2012
DOI: 10.1073/pnas.1206598109
|View full text |Cite
|
Sign up to set email alerts
|

Unifying the spatial epidemiology and molecular evolution of emerging epidemics

Abstract: We introduce a conceptual bridge between the previously unlinked fields of phylogenetics and mathematical spatial ecology, which enables the spatial parameters of an emerging epidemic to be directly estimated from sampled pathogen genome sequences. By using phylogenetic history to correct for spatial autocorrelation, we illustrate how a fundamental spatial variable, the diffusion coefficient, can be estimated using robust nonparametric statistics, and how heterogeneity in dispersal can be readily quantified. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
350
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(391 citation statements)
references
References 42 publications
18
350
0
3
Order By: Relevance
“…Although we have documented some evidence that phylogenetic structure is shaped by avian flyway, a pattern that has also been observed for avian influenza virus (51), it is difficult to distinguish the impact of avian flyway from other geographic effects on these data. It is also likely that long distance viral movements, rather than simple homogenous dispersal, have impacted the continental spread of WNV (52). Interestingly, the relatively weak geographical clustering observed here is in contrast to the pattern seen for St. Louis encephalitis virus (SLEV), the only other avian arthropod-borne virus known be associated with encephalitis in humans in the United States prior to the emergence of WNV and that was first isolated in 1933 (53,54).…”
Section: Discussionmentioning
confidence: 55%
“…Although we have documented some evidence that phylogenetic structure is shaped by avian flyway, a pattern that has also been observed for avian influenza virus (51), it is difficult to distinguish the impact of avian flyway from other geographic effects on these data. It is also likely that long distance viral movements, rather than simple homogenous dispersal, have impacted the continental spread of WNV (52). Interestingly, the relatively weak geographical clustering observed here is in contrast to the pattern seen for St. Louis encephalitis virus (SLEV), the only other avian arthropod-borne virus known be associated with encephalitis in humans in the United States prior to the emergence of WNV and that was first isolated in 1933 (53,54).…”
Section: Discussionmentioning
confidence: 55%
“…We confirm that deterministic models can be applied to describe ecological processes and show that additional information on the stochasticity acting at the mesoscopic scale allows us to estimate fluctuations at the macroscopic scale. We believe that our results might have implications for the dynamics of phenomena other than species' invasions, such as morphogenesis (23,47), tumor growth (23,25,36), and the spreading of epidemics (23,30,34,35), which have been traditionally modeled with reaction-diffusion equations.…”
Section: Discussionmentioning
confidence: 87%
“…Modeling of biological dispersal established the theoretical framework of reaction-diffusion processes (1-3, 23-25), which now finds common application in dispersal ecology (5,14,22,(26)(27)(28)(29)(30) and in other fields (17,23,25,(31)(32)(33)(34)(35)(36). Reaction-diffusion models have also been applied to model human colonization processes (31), such as the Neolithic transition in Europe (25,37,38).…”
mentioning
confidence: 99%
“…It remains unclear whether the risk of TBD propagates locally, generating a rabies disease-like invasion front [11,16] or if TBD risk is driven by long-distance dispersal as occurs for West Nile Virus fever [28]. Although several studies have identified possible ecological correlates of TBD prevalence in humans, including density of infected ticks [29], and correlates of the distribution of infected ticks, including proximity to water bodies [30] and, for babesiosis, prevalence of Lyme disease [31], the ecological factors driving spread of reported TBD at the scale of the northeast United States remain unresolved.…”
Section: Introductionmentioning
confidence: 99%